Classical Liberalism and Self-Reference Approach In Dealing With Harmonisation ASEAN IPR Regulations - Rizki Rahmadini Nurika; Septian Nur Yekti (Sospol : Jurnal Sosial Politik, 2019)
ASEAN Economic Community (AEC) regulates the Intellectual Property Rights (IPR) in its relation with their economic activities. It was stipulated in the ASEAN Framework Agreement on Intellectual Property Cooperation in 1995. As the ASEAN member states are also the member of World Trade Organization (WTO), the principles of AEC have to be in harmony with the WTO principles. This paper analyzes the compliance of ASEAN IPR laws with the principles of Trade Related to Intellectual Property Rights (TRIPs) of WTO. Second, this paper analyzes the enforcement of those regulations in the member states, finding out whether there is implementation in the region that is different with the international principles or not. It is a part of qualitative research that used secondary data to complete the explanative analysis. Classical liberalism and self-reference criterion becomes theoretical framework of analysis. Classical liberalism promotes laissez-faire economics and private property in the means of production. Meanwhile, self-reference criterion refers to an unconscious reference to one’s own culture, values, knowledge, and experience as a basis for decisions. The result reveals that the ASEAN IPR regulations have different specific and special nature with the TRIPs, affected by the characteristics of the nations.